From biology to surgery: One step beyond histology for tailored surgical treatments of gastric cancer. (September 2020) - Fiorillo, Claudio; Laterza, Vito; Quero, Giuseppe; Menghi, Roberta; Cina, Caterina; Rosa, Fausto; Tortorelli, Antonio Pio; Boskoski, Ivo; Alfieri, Sergio
Abstract: Gastric cancer is the third most common cause of cancer related death. Although its incidence is globally declined, prognosis remains dismal in the Western hemisphere, while better outcomes are evidenced in Asian countries. Endoscopic or surgical resection with or without lymphadenectomy represents the only chance of cure, with limited improvements of the prognosis in case of associated chemotherapy in a neoadjuvant or adjuvant setting. This could be mainly attributed to the uniform fashion of treatment of gastric cancer, mainly based on the histological features, that usually do not reflect the complexity of the disease. With the recent introduction of genomic technologies and new generation sequencing techniques, gastric cancer biology is now investigated in great details. This has brought to the publication of three main molecular classifications, based on the underlying molecular biology of gastric cancer. Although only few clinical reports are currently present in literature, the identification of gastric cancer molecular subtypes has shown interesting findings that may pave the way to a tailored clinical and surgical management. The aim of this review is, thus, to give a comprehensive overview of the current molecular classifications as compared to the available histopathological ones, also focusing on the potential clinical and surgical benefits and the future perspectives for a more personalized treatment of gastric cancer. Highlights: New technologies have brought to a deeper investigation of gastric cancer biology. Three main molecular classifications are currently present in the literature. Few evidences are reported on the clinical application of the new molecular classifications. Their use in the near future could potentially path the way to tailored treatments of gastric cancer.